Design Of Teaching Materials With A Scientific Approach On Algebraic Forms Of Middle School Vii Class Materials - Agus, Agus; Aripin, Usman ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
This study aims to determine the accuracy of the product of LIP and SW teaching materials with a scientific approach to Algebraic material for junior high school students and the validity of teaching materials developed based on expert validation. The method used in this research is development research which leads to two stages of implementation, the first is to design teaching materials based on a scientific approach. And the second validates the teaching material products that have been made. The results of this study develop teaching materials that were developed after being validated by expert validators and field practitioners and supported by articles that support the results of the validation of the Learning Implementation Plan (LIP) and Student Worksheet (SW). The final criteria are good and are in the valid category. This means that the teaching materials are worthy of being tested in learning.